Conceptualizing and capturing digital transformation's customer value: A logistics and supply chain management perspective - Anna Lisa Junge (Universitätsverlag der TU Berlin, 2020)
This thesis aims to add knowledge that contributes to answering the question of how digital transformation technologies can contribute to increasing customer value in logistics and supply chain management (L&SCM), and how manufacturing companies can mindfully use them. The output of the thesis is an architectural framework that proposes performance components, approaches and methodologies that can help in capturing this customer value. To build the basis for such a framework, this research first deduces and presents the underlying definition of digital transformation and describes its potential for, as well as current barriers for its application in, L&SCM. The study uses a systematic literature review to identify nine underlying digital transformation technology bundles. These are: auto-identification technologies; information and communication technologies; the cloud; cyber physical systems; analytics; distributed ledger; automation technologies; augmented and virtual reality; and additive manufacturing. These technologies served as inputs for a nominal group technique workshop aiming to conceptualize the dimensions of customer value based on the technologies. The derived dimensions are information disclosure, time, product/production, service/assistance, quality, choice options, and planning. Based on these findings, this thesis presents an impact assessment for customer-based L&SCM performance. The three-plus-one customer value propositions are availability, servitization, co-creation, and cognition as enhancement. Expert interviews provide the data for the architectural framework for capturing customer value based on digital transformation technologies in L&SCM. The six dimensions covered are the customer value proposition; the value portfolio; scope of collaboration; human resource management and organization; performance management; as well as the (re-)adjusting value assessment. The main scientific contribution lies in conceptualizing the customer value for L&SCM based on digital transformation technologies whereas the architectural framework constitutes the main practical contributions. – – Ziel dieser Arbeit ist es, die Frage zu beantworten, wie digitale Transformationstechnologien dazu beitragen und bewusst eingesetzt werden können, um den Kundennutzen in Logistik und Supply Chain Management (L&SCM) von produzierenden Unternehmen zu erhöhen. Das Ergebnis ist ein architektonischer Rahmen, der Leistungskomponenten, Ansätze und Methoden vorschlägt, wie dieser Kundenmehrwert erfasst und umgesetzt werden kann. Um die Grundlage für das Framework zu schaffen, leitet diese Arbeit zunächst die zugrunde liegende Definition für digitale Transformation ab und beschreibt deren Potentiale sowie die aktuellen Barrieren für L&SCM. Die relevanten neun digitalen Transformationstechnologiebündel werden auf Basis einer systematischen Literaturanalyse identifiziert. Es handelt sich um Technologien zur automatischen Identifizierung, Informations- und Kommunikationstechnologien, Cloud, cyberphysikalische Systeme, Analytics, Distributed Ledger, Automatisierungstechnologien, Augmented und Virtual Reality sowie Additive Fertigung. Diese Technologien dienen als Input für einen Nominal Group Technique-Workshop, der darauf abzielt, die Dimensionen des Kundennutzens auf der Grundlage dieser Technologien zu konzeptualisieren. Die abgeleiteten Dimensionen sind Informationsverfügbarkeit, Zeit, Produkt/Produktion, Service und Assistenzsysteme, Qualität, Auswahlmöglichkeiten und Planung. Auf der Grundlage dieser Ergebnisse wird ein Einflussmodell für kundenorientierte L&SCM Leistungen vorgestellt. Die drei plus eins Kundenwertversprechen sind Verfügbarkeit, Service, Ko-Kreation und Kognition als Zusatzkomponente bzw. Erweiterung. Experteninterviews dienen als Datenbasis für das architektonische Framework zur Erfassung des Kundennutzens auf der Grundlage digitaler Transformationstechnologien in L&SCM. Die sechs abgedeckten Dimensionen sind das Kundenwertversprechen, das Wertportfolio, Kollaboration, Personalmanagement und Organisation, Leistungsmanagement sowie die Erfassung und Bewertung des Kundenwertes. Der wichtigste wissenschaftliche Beitrag liegt in der Konzeption des Kundennutzens für L&SCM auf der Grundlage digitaler Transformationstechnologien, während der wichtigste praktische Beitrag in dem architektonischen Framework zu sehen ist.
Keywords: 650; logistics; supply chain management; digital transformation; customer value; innovation; Logistik; digitale Transformation; Kundenwert; Innovation